A Reproducible IT-Blog Corpus. (22nd July 2021) - Barbaresi, Adrien; Pohlmann, Jens
The dataset comprises text and metadata extracted from several hundred IT-blogs and websites, along with a method to duplicate the data by updating its contents and downloading it to the user's local machine. The targets have been hand-picked with the intention to represent the discourse on blogs and websites dedicated to questions at the intersection of technology and society from Germany and the United States of America. The texts have been retrieved by web crawling techniques. The resulting corpus is accessible through a search platform and also reproducible with freely accessible descriptors and software.